Improving the thermostability of alginate lyase FlAlyA with high expression by computer-aided rational design for industrial preparation of alginate oligosaccharides - Zhang, Xiu; Li, Wei; Pan, Lixia; Yang, Liyan; Li, Hongliang; Ji, Feng; Zhang, Yunkai; Tang, Hongzhen; Yang, Dengfeng (Frontiers in Bioengineering and Biotechnology, 2022)
FlAlyA, a PL7 alginate lyase with industrial potential, is widely applied in the preparation the alginate oligosaccharide because of its high activity of degradation the alginate. However, heat inactivation still limits the industrial application of FlAlyA. To further enhance its thermostability, a group of mutants was designed and evaluated the B-factor value and free energy change via computer-aided calculation. 25 single-point mutants and 1 double-points mutant were carried out by site-directed mutagenesis. The optimal single-point mutants H176D and H71K showed 1.20°C and 0.3°C increases in the values of Tm, while 7.58 minutes and 1.73 minutes increases in the values of half-life (t1/2) at 50°C, respectively, compared with that of the wild-type enzyme. Interestingly, H71K exhibits the comprehensive improvement than WT, including expression level, thermal stability and specific activity. In addition, the mechanism of these two mutants is speculated by multiple sequence alignment, structural basis and molecular dynamics simulation, which is likely to be involved in the formation of new hydrogen bonds. These results indicate that B-factor is an efficient approach to improves the thermostability of alginate lyase composed of β-sheet unit. Furthermore, the highest yield of recombinant enzyme FlAlyA reached 600 mg/L, which provided the possibility for the industrial production of alginate oligosaccharides.